Preparation and Property of Paraffin/CaCO3 Composite as Form-Stable Phase Change Material for Thermal Energy Storage - Li, Benxia; Liu, Tongxuan; Wang, Yanfen (Asian Journal of Chemistry, 2012)
In this work, a paraffin/CaCO3 composite phase change material with a paraffin capacity of 50 wt % was prepared using a microemulsion method. The paraffin was used as the phase change material for thermal energy storage and CaCO3 served as the supporting material for improving the thermal stability of the composite. The as-obtained composite was characterized by X-ray diffractometer, Fourier transformation infrared spectroscopy, scanning electronic microscopy and differential scanning calorimeter. The composite can maintain its original shape perfectly without any paraffin leakage after subjected to 30 melt-freeze cycles, in which the paraffin was well dispersed in the porous network of CaCO3, observed by SEM.